Comparative study of intravenous opioid consumption in the postoperative period - Saracoglu, Kemal Tolga; Saracoglu, Ayten; Cakar, Kubra; Fidan, Vural; Ay, Binnaz (Biomedical papers, 2012)
Background: Intravenous patient-controlled analgesia (IV PCA) using opiods is an accepted method for delivering postoperative analgesia. The aim of this study was to compare fentanyl and tramadol with IV PCA after spinal anesthesia (SA) and general anesthesia (GA) following cesarean section (C/S).Methods: Ninety women were randomly assigned to three groups (n=30). Group 1 was treated with IV fentanyl PCA after SA. Groups 2 and 3 were treated with IV fentanyl PCA and IV tramadol PCA after GA. Outcome measures were recorded for the first 24 h post-anesthesia.Results: PCA use was significantly lower after SA (P<0.05). Eighteen patients in the SA Group and 27 patients and 24 patients from the GA groups required additional opioid. Opioid consumption and patient satisfaction were similar for groups after GA (P>0.05). 638.4 ± 179.1 μg fentanyl was consumed by patients of Group 2, 356.3 ± 87.0 μg fentanyl and 559.5 ± 207.0 mg tramadol was consumed by Group 1 and Group 3 respectively. There was no significant difference in the overall severity and incidence of nausea, drowsiness or pruritus.Conclusion: Our study shows that analgesic consumption and post-operative pain scores after SA in C/S decreased, without increase in adverse reactions.
Keywords: patient-controlled analgesia; fentanyl; tramadol; spinal anesthesia